Good Corporate Governance dan Corporate Social Responsibility Terhadap Kinerja Keuangan pada Perusahaan yang Terdaftar di Indeks Sri-Kehati Periode 2019-2024 - Alya Apriyolandini; Rosmini Ramli (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to examine the influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on financial performance among companies listed on the SRI-KEHATI Index during the 2019–2024 period. GCG is proxied by managerial ownership, board of commissioners, audit committee, board of directors, and institutional ownership, while financial performance is measured using Return on Assets (ROA). This research adopts a quantitative approach, supported by secondary data obtained from companies’ annual and sustainability reports. Data analysis techniques include descriptive statistics, classical assumption testing, and panel data regression analysis using EViews version 12. The findings reveal that: (1) managerial ownership and audit committee have a negative influence on financial performance, while (2) board of commissioners and board of directors have a positive influence. These results suggest that not all components of GCG and CSR implementation directly impact financial performance. The effectiveness of these practices largely depends on the quality of implementation within each company.